Enemy-mediated apparent competition: empirical patterns and the evidence - Chaneton, Enrique J.; Bonsall, Michael B. (Oikos, 2000)
Apparent competition arises when two victim species negatively affect each other (-, -) by enhancing the equilibrium density or changing the foraging behaviour of a shared natural enemy. Shared enemies can also mediate non-reciprocal (-, 0) indirect effects, i.e. indirect amensalism, whenever one prey species is not affected by the presence of alternative prey. We review 34 studies on terrestrial and freshwater systems to evaluate the extent to which apparent competition has been perceived as a reciprocal (-, -) or non-reciprocal (-, 0) interaction. We found only three studies showing reciprocal effects between apparent competitors. Indirect amensalism was documented in 10 studies and could be inferred for 16 other cases (76% in total). The remaining five studies provided insufficient data to determine the form of indirect interaction. The apparent prevalence of non-reciprocal enemy-mediated interactions resembles that observed for resource-based interspecific competition. Amensal indirect effects via shared predation may result from differences in population size, nutritional value, susceptibility to attack, or asynchronous dynamics of alternative prey, or the predator's feeding preferences. Moreover, experimental protocols may confound the actual form of apparent competition through short-term observations, incomplete designs, or biased consideration of conspicuous interactions, leading to reciprocal effects being overlooked. We conclude that, at present, it is still difficult to determine the relative role of apparent competition vs indirect amensalism in natural food webs because most published studies have failed to document in full interactions via shared enemies.